Toxic effect of Chloropyrpheos, Deltamethrinand Dimethoate on biochemical parameters in male rabbits. (Journal of Medical Sciences, 2023)
Dimethoate, deltamethrin and chloropyrfios are three of widely used organophosphorus insecticides in agriculture. The irrational use of Dimethoata, deltamethrin  and chlyropyrfios in Libya play a crucial role in the occurrence of many diseases affecting plants, animals and the environment. The present work was conducted to investigate the alterations in biochemical parameters  in male rabbits after orally administration a single dose of dimethoate (DM) by gavage at a dose of 43.2 mg/kg B.W/day (1/50 of DM) lethal dose, deltamethrin by gavages at a dose of 1.28 mg/kg B.W/day (1/50 of DM) lethal dose and chloropyrfios by gavages at a dose of 33.3 mg/kg B.W/day (1/50 of CPF) lethal dosefor 12-week.Twenty Male Rabbits weighting(1.89127.6 Kg),  were divided into four groups with 5 animals in each, first group served as control animals, they received 5 ml of corn oil, while animals in second group received Dimethoate, animals in third group received of deltamethrin and animals in fourth  group received of chloropyrfios.Results obtained showed that all pesticide  significantly (P < 0.05) induced  Aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (AlP) activities were increased (P < 0.05). All pesticide significantly (P < 0.05) increased the levels of plasmaglucose, urea , creatinine and total bilirubin. Conclusion, A pervasively-used dimethoate, deltamethrin and chloropyrfios helps in minimizing the damages caused by pests, but its exposure could be harmful for animal as well as human population. The present investigation provides an insight of dimethoate, deltamethrin and chloropyrfiosinduced toxicity on biochemical  parameters.